Astonishing splashes of colour - Morrall, Clare (London : Sceptre, 2013)
A compelling and affecting tale of a woman whose longing to have children and for the mother she never knew leads her into serious trouble.
Keywords: Identity (Psychology) -- Fiction; Psychological fiction